2007
DOI: 10.1177/030089160709300603
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Lymphomaand Hepatitis B Virus/Hepatitis C Virus Infections in the Region of East Black Sea, Turkey

Abstract: Our findings suggest that the incidence of HBV and HCV infections in lymphoma patients is no different than that of nonlymphoma patients. Therefore, no direct correlation can be deduced between lymphoma and HBV-HCV infections in our East Black Sea region of Turkey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…These three DNA viruses have already shown to play an important role in the pathogenesis of different cancers through their interference with cellular DNA repair mechanisms [5][6][7]. We found that the prevalence of HBV, HSV1 and EBV was significantly higher in those who were diagnosed to have ALL.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…These three DNA viruses have already shown to play an important role in the pathogenesis of different cancers through their interference with cellular DNA repair mechanisms [5][6][7]. We found that the prevalence of HBV, HSV1 and EBV was significantly higher in those who were diagnosed to have ALL.…”
Section: Discussionmentioning
confidence: 60%
“…Defective or inhibited repair of DNA breaks will results in translocations (the hallmark genetic mutations of ALL) and this is a key step in pathogenesis of ALL. Previous studies have shown that some DNA viruses' infection, notably herpes viruses, Epstein-Barr virus (EBV) and Hepatitis B virus (HBV) interferes with cellular DNA repair mechanisms [5][6][7] and could lead to these characteristic genetic changes. Previous studies tried to determine the association between prenatal virus infections and development of pre-leukemic cells containing characteristic translocations; however they showed no association between infection with polyoma viruses [8], herpesviruses [9,10], or parvovirus B19 [11] and childhood ALL.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported a significant association between chronic HBV infection and non-Hodgkin's lymphoma (NHL), mainly in HBV endemic areas, [1][2][3][4][5] while some controversial results on the association in different geographic areas have been reported. 6,7 The clinical course and outcome of chronic HBV infection is determined by the interplay between virus replication and the host immune response. 8 Immunosuppressive therapy, including anticancer systemic chemotherapy, can induce HBV replication and reactivation of hepatitis B, which may lead to hepatitis flare and even hepatic failure, in hematologic malignancy, such as NHL and leukemia, as well as solid cancers.…”
Section: Introductionmentioning
confidence: 99%
“…However, Isikdogan et al [13] found no association in 119 NHL patients. Similarly, Timuraglu et al [14] and Sonmez et al [15] identified no association. Summarizing the results from across Turkey, all that can be stated is that the evidence in inconclusive (Tables 5, 6).…”
Section: Discussionmentioning
confidence: 91%